AAGBS strives for excellence in Assurance of Learning (AoL) workshop - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS, 2024)
Over the past two days (19-20 September 2024), faculty members from Arshad Ayub Graduate Business School (AAGBS), including those from the Shah Alam main campus and various branch campuses, came together for a comprehensive Assurance of Learning (AoL) Workshop 20242 for Cycle1 Year1 (C1Y1). This workshop aimed to further elevate the quality of teaching delivery across our MBA, MIBF, DBA, and PhD programmes. The workshop, led by our esteemed AoL Chairperson, Assoc. Prof. Dr. Siti Zaleha Sahak, and featuring opening remarks from AAGBS Dean, Professor Dr. Norzanah Mat Nor. A Brief explanation about reporting, discussion, and strategic alignment by Assoc. Prof. Dr. Wahida Ahmad (Head of Postgraduate Studies) and Assoc. Prof. Dr. Hadijah Iberahim (Head of Quality Management). Faculty members engaged in insightful sessions, addressing program-specific assurance, and sharing ideas on innovative methods to enhance learning outcomes. The AoL workshop reflects AAGBS continuous commitment to upholding academic excellence and adapting to the evolving needs of our students and the industry. With contributions from our dedicated faculty members, resource persons, and AoL committees, this collaborative effort ensures that our graduate programs remain competitive, impactful, and student-centered. Thank you to all faculty members from all branches and campuses for joining the workshop. We look forward to seeing the positive outcomes from this workshop, as we continue to nurture the next generation of business leaders and professionals.